2020
DOI: 10.1038/s41598-020-67042-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field assisted high capacity durable Li-ion battery using magnetic α-Fe2O3 nanoparticles decorated expired drug derived N-doped carbon anode

Abstract: We have synthesized a novel ferromagnetic material by coating α-Fe 2 o 3 nanoparticles with N-doped carbon matrix using a simple combustion method. Expired paracetamol drugs are used as nitrogen and carbon source. This α-Fe 2 o 3 /NC shows ferromagnetic property due to the incorporation of oxygen defects. When used as the Li-ion battery anode, α-Fe 2 o 3 /NC shows higher capacity compared to commercial α-Fe 2 o 3 due to the occurrence of both intercalation and conversion reaction. Further, application of magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Some experimental studies, such as that performed by Ganguly et al. ( Ganguly et al., 2020 ), demonstrate how an external field over a α-Fe 2 O 3 /NC anode battery enhances the first and second cycle CE from 70% (without applied MF) to 73.5% (with field), on the first cycle. Moreover, the increasing of the specific capacity from 1500 to 1700 mAh/g and from 1100 to 1300 mAh/g for a density of current of 50 mA/g , on first and second discharge cycle, respectively, was observed.…”
Section: Coupling Of Mfs and Lithium-ion Battery – Hall Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…Some experimental studies, such as that performed by Ganguly et al. ( Ganguly et al., 2020 ), demonstrate how an external field over a α-Fe 2 O 3 /NC anode battery enhances the first and second cycle CE from 70% (without applied MF) to 73.5% (with field), on the first cycle. Moreover, the increasing of the specific capacity from 1500 to 1700 mAh/g and from 1100 to 1300 mAh/g for a density of current of 50 mA/g , on first and second discharge cycle, respectively, was observed.…”
Section: Coupling Of Mfs and Lithium-ion Battery – Hall Effectmentioning
confidence: 98%
“…Consequently, the charging cycles process of the battery, at its beginnings, depends essentially on the creation of the layer of the SEI (Miura et al, 2017), since the electrolyte is protected by the SEI film, avoiding an increased exhaustion and the anode from corrosion since vigorous reactions arise between electrolyte material and anode material at the initial battery charging processes (Miura et al, 2017). Some experimental studies, such as that performed by Ganguly et al (Ganguly et al, 2020), demonstrate how an external field over a a-Fe 2 O 3 /NC anode battery enhances the first and second cycle CE from 70% (without applied MF) to 73.5% (with field), on the first cycle. Moreover, the increasing of the specific capacity from 1500 to 1700 mAh/g and from 1100 to 1300 mAh/g for a density of current of 50 mA/g , on first and iScience Review second discharge cycle, respectively, was observed.…”
Section: Manipulation Of Lib By An Applied Mfmentioning
confidence: 99%
“…This allows the hydroxyl ions to be transported faster, while limiting the H + ions transport in electrode‐electrolyte interface 33 . The applied magnetic field on α‐Fe 2 O 3 nanoparticles anode has doubled the specific capacity of a Li‐ion battery from 80 to 150 mAh g −1 due to the faster kinetics in Li + ions transport 34 . Another report shows fast charging Li‐ion graphite battery gain 22% additional capacity under the ambiance of external magnetic field 35 .…”
Section: Introductionmentioning
confidence: 99%
“…33 The applied magnetic field on α-Fe 2 O 3 nanoparticles anode has doubled the specific capacity of a Li-ion battery from 80 to 150 mAh g À1 due to the faster kinetics in Li + ions transport. 34 Another report shows fast charging Li-ion graphite battery gain 22% additional capacity under the ambiance of external magnetic field. 35 Paramagnetic lithium ions in aqueous electrolytes solution experience MHD force as a result of spin vortex of magnetic poles interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, there have been few studies on energy storage technologies such as supercapacitors and Li-batteries, where appreciable modifications in the electrochemical performance have been reported. These effects are quite prominent in supercapacitors fabricated using metal oxides that have at least one magnetic ion. Most of the authors, including us, have attributed the change to the changing Lorentz force and/or magneto-hydrodynamic effects. However, the literature lacks a suitable theoretical model that explains the experimental data and incorporates the impact of the radius of electrolyte’s ion, which is critical in the case of magnetic supercapacitors.…”
Section: Introductionmentioning
confidence: 99%